2000
DOI: 10.1128/jvi.74.12.5432-5440.2000
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of Dextran Sulfate 500, the Polyene Antibiotic MS-8209, and Congo Red on Accumulation of the Protease-Resistant Isoform of PrP in the Spleens of Mice Inoculated Intraperitoneally with the Scrapie Agent

Abstract: The mode and the site of action of the major antiscrapie drugs have been studied by investigating their effects on the abnormal protease-resistant isoform of PrP (PrPres) and on its accumulation in mouse spleen. Dayby-day PrPres accumulation in the spleen and in other peripheral organs was first monitored to describe the early steps of scrapie pathogenesis. Three phases were identified: the detection of scrapie inoculum on the day of scrapie infection, a clearance phase, and then the peripheral accumulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 49 publications
4
60
0
1
Order By: Relevance
“…Not only have direct interactions been demonstrated with PrP (14,15), GAGs have been shown to influence PrP sc accumulation in both cell-culture and in vitro converting experiments (12-13, 17, 18) and to modulate PrP sc propagation and disease onset in animal models for scrapie (8,9). This study has addressed three areas of current interest: the structural features of GAGs that engender PrP-binding ability, the influence of metal ions on GAG binding, and the location of GAG binding domains within PrP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only have direct interactions been demonstrated with PrP (14,15), GAGs have been shown to influence PrP sc accumulation in both cell-culture and in vitro converting experiments (12-13, 17, 18) and to modulate PrP sc propagation and disease onset in animal models for scrapie (8,9). This study has addressed three areas of current interest: the structural features of GAGs that engender PrP-binding ability, the influence of metal ions on GAG binding, and the location of GAG binding domains within PrP.…”
Section: Discussionmentioning
confidence: 99%
“…On a weight/volume basis this preparation was found to be superior to heparin and at least as effective as pentosan polysulfate (PPS), a polyanion with well-documented anti-prion activities in tissue culture and animal models (7,36). It would be of great interest to compare the inhibitory activity of DS8 with fractions of higher molecular weight such as DS500 (average molecular weight 500,000), which is a particularly effective inhibitor of PrP sc propagation in cell culture (13) and a potent anti-prion agent in animal studies of prion disease (8,9). Using this competition ELISA we also explored the contribution to prion binding of 2-and 6-O sulfate groupings, two of the three types of sulfate that elaborate heparin and HS (Nsulfates were not examined in this study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the extent of the vCJD epidemic in forthcoming years is still uncertain (Ghani et al, 2000(Ghani et al, , 2002, and given that no effective treatments are presently available for TSEs, the development of new therapeutic strategies is of crucial importance. One class of molecules that has shown significant efficiency in the treatment of prion diseases is the class of sulfated polyanions, such as dextran sulfate 500 (DS500), pentosane polysulfate and suramin (Farquhar & Dickinson, 1986;Kimberlin & Walker, 1986;Ladogana et al, 1992;Caughey & Raymond, 1993;Beringue et al, 2000;Gilch et al, 2001). However, their use is limited by their toxicity, restricted efficiency and narrow window of intervention following infection (Diringer & Ehlers, 1991;Ladogana et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Time-course analyses of peripheral PrP Sc accumulation in mice confirmed that PrP Sc was detectable in the spleens at 7 days and reached a plateau by 30-40 days after peripheral challenge (Beringue et al, 2000).…”
mentioning
confidence: 96%